2020
DOI: 10.1177/0003134820943547
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Approach to Hiatal Hernia Repair: Results After 7 Years of Robotic Experience

Abstract: Introduction Robotic hiatal hernia repair offers potential advantages over traditional laparoscopy, most notably enhanced visualization, improved ergonomics, and articulating instruments. The clinical outcomes, however, have not been adequately evaluated. We report outcomes of laparoscopic and robotic hiatal hernia repairs. Methods A retrospective observational cohort study was performed of all hiatal hernia repairs performed from 2006 through 2019. Operative, demographic, and outcomes data were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…TAPP umbilical surgery now commonly involves the use of surgical robots that make this procedure much easier. First, they allow for very good visualization of all prepared layers while maintaining continuous hemostasis, minimizing hand tremors and excessive movements, prevent damage to the thin peritoneal lamina, and after preparing the appropriate space they allow for quick, reliable, and convenient closure of the hernia and peritoneal defects [17]. For these reasons, many surgeons believe that this is an operation that should only be performed in centers equipped with robotic systems [18].…”
Section: Discussionmentioning
confidence: 99%
“…TAPP umbilical surgery now commonly involves the use of surgical robots that make this procedure much easier. First, they allow for very good visualization of all prepared layers while maintaining continuous hemostasis, minimizing hand tremors and excessive movements, prevent damage to the thin peritoneal lamina, and after preparing the appropriate space they allow for quick, reliable, and convenient closure of the hernia and peritoneal defects [17]. For these reasons, many surgeons believe that this is an operation that should only be performed in centers equipped with robotic systems [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown robotic approach to gastrointestinal surgery provides enhanced visualization, more precise dissection of tissue planes, and better articulation of instruments. 11,12 In particular, specific advantages robotic surgery provides for foregut surgery include better tissue manipulation for creating intracorporeal anastomosis and longer instruments allowing easier dissection in the mediastinum. Factors regarding location of anastomosis and type of anastomosis created may also explain the occult nature of anastomotic leaks observed after robotic esophagectomies.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 10 It is crucial to perform partial fundoplication to avoid reflux disease, protecting the esophageal mucosa from possible complications. 12 15 …”
Section: Discussionmentioning
confidence: 99%
“…4,10 It is crucial to perform partial fundoplication to avoid reflux disease, protecting the esophageal mucosa from possible complications. [12][13][14][15] The main complications of surgical treatment are empyema, abscesses, and fistulas; which must be quickly identified and treated. In addition, failure to perform esophageal myotomy may result in a high-pressure zone of the staple line of the resected diverticulum, causing it to rupture.…”
Section: Discussionmentioning
confidence: 99%